Process for preparing ceramic substrate by tape casting method
The ceramic substrate is prepared by casting method, and the fibrous structure and annealing treatment of the biological template are solved, and the ceramic substrate is prone to cracking or breaking, which significantly improves its toughness and flexural strength and enhances structural stability.
Patent Information
- Application Number
- CN202411910277.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
Existing ceramic substrates are prone to cracking or breaking when subjected to external forces, resulting in insufficient toughness and flexural strength, affecting reliability and stability.
The ceramic substrate is prepared by casting method. Through pretreatment, biological treatment, casting molding, drying, presintering, sintering treatment and other steps, the fiber-like structure and annealing treatment of the biological template are used to enhance the toughness and flexural strength of the ceramic substrate.
It significantly improves the toughness and flexural strength of the ceramic substrate, enhances its structural stability, and improves its performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic substrates, in particular to a tape casting method for preparing ceramic substrates. Background Art
[0002] Currently, commonly used electronic packaging materials mainly include four categories: plastic substrates, metal substrates, ceramic substrates and composite substrates. Among them, ceramic substrates have excellent electrical insulation properties, high thermal conductivity, excellent soft soldering performance and high adhesion strength, and can be etched with various patterns like PCB boards. They have a large current-carrying capacity. Therefore, ceramic substrates are widely used in high-power power semiconductor modules, power control circuits, automotive electronics, aerospace, military electronic components, and solar panel components.
[0003] In the prior art, such as the Chinese patent: CN118754620A, a method for preparing a ceramic substrate and a ceramic substrate, the method for preparing a ceramic substrate includes the following steps: drying alumina powder to control the water content of the alumina powder to be less than 0.1%; grinding and mixing the dried alumina powder with a dispersant, a plasticizer, a binder, and a solvent to obtain a slurry; casting the slurry to form a green porcelain tape; stacking the green porcelain tape, and then performing vacuum isostatic pressing and sintering in sequence to obtain a ceramic substrate. The technical solution of the present invention controls the water content of the alumina powder to be less than 0.1%, which can avoid the generation of a large amount of gas during sintering, thereby avoiding the formation of stress cracks inside the substrate and ensuring the sintering yield.
[0004] In the above patent, although a binder is added during the preparation process, its main function is to enable the alumina powder to be better combined together in the slurry stage, and its contribution to improving the toughness of the ceramic substrate when subjected to external force is limited, resulting in the toughness of the finished ceramic substrate being limited. When subjected to external force impact, it is easy to crack or break, thereby reducing the reliability and stability of the ceramic substrate. Based on this, the present invention provides a tape casting preparation process for a ceramic substrate. Summary of the invention
[0005] The purpose of the present invention is to provide a tape casting process for preparing a ceramic substrate. The ceramic substrate prepared by the present invention not only has toughness and flexural strength, but also has excellent structural stability, thereby effectively improving the performance of the ceramic substrate.
[0006] To achieve the above object, the present invention provides the following technical solution: A tape casting process for preparing a ceramic substrate comprises the following steps:
[0007] S1: Pretreatment, selecting high-purity ceramic powder, and placing it in a vacuum oven at 80-120°C for 4-8 hours to remove moisture and residual impurities, then adding the high-purity ceramic powder to the mixed liquid and stirring evenly to obtain a ceramic slurry;
[0008] S2: biological treatment, adding the biological template to the ceramic slurry, stirring and defoaming, and completing the biological treatment of the ceramic slurry;
[0009] S3: tape casting, placing the ceramic slurry in a tape casting machine for tape casting to obtain a ceramic green film;
[0010] S4: drying and pre-sintering treatment, drying and pre-sintering treatment of the ceramic green membrane obtained in S3, completing the drying and pre-sintering treatment of the ceramic green membrane;
[0011] S5: sintering treatment, cutting the ceramic green sheet that has completed the drying and pre-sintering treatment in S4, and then passing it through a debinding furnace, a high-temperature sintering furnace and an annealing furnace to complete debinding, sintering and annealing treatment, and then taking it out to obtain a ceramic substrate.
[0012] Furthermore, the mass ratio of the mixed liquid to the ceramic powder is 1:(7-9), wherein the mixed liquid is composed of a dispersant, a binder, a plasticizer and a solvent, and the mass ratio thereof is 1:4:2:3.
[0013] Furthermore, the dispersant is at least one of ammonium polyacrylate or sodium dodecyl sulfate, the binder is at least one of polyvinyl alcohol or polymethyl methacrylate, the plasticizer is at least one of dibutyl phthalate or polyethylene glycol, and the solvent is at least one of ethanol or toluene.
[0014] Furthermore, the high-purity ceramic powder is at least one of aluminum oxide powder, aluminum nitride powder or zirconium oxide powder.
[0015] Furthermore, the biological template is made by the following method: bamboo is selected as the material, external dust and debris are removed by water washing, and then the bamboo is soaked in a sodium hydroxide solution for 10-30 minutes, wherein the concentration of the sodium hydroxide solution is 1%-3%, and then cut into long strips by a cutting machine to obtain the biological template.
[0016] Furthermore, after cutting, the bio-template has a length of 3-5 cm, a width of 3-5 cm and a thickness of 1-2 mm.
[0017] Furthermore, the biological treatment step is: adding the bio-template into the ceramic slurry for soaking, wherein the mass ratio of the bio-template to the ceramic slurry is 1:(8-10), and using a stirrer for auxiliary stirring, the stirring speed is 300-500r / min, stirring for 1-2h, then taking out the fully soaked ceramic slurry containing the bio-template, placing it in a vacuum box for degassing treatment, evacuating to a pressure below 500Pa, and the duration is 20-25min, thereby completing the biological treatment of the ceramic slurry.
[0018] Furthermore, the drying and pre-sintering treatment method is to place the ceramic green membrane in a drying oven, dry it for 10-20 hours at a temperature of 20-40°C and a relative humidity of 25-45%, then take out the dried ceramic green membrane, put it into a pre-sintering furnace, heat it to 400-600°C at a heating rate of 2-6°C / min in an air atmosphere, and keep it warm for 1-3 hours, thereby completing the drying and pre-sintering of the ceramic green membrane.
[0019] Furthermore, the sintering treatment method is to cut the dried and pre-sintered ceramic green sheet as needed, then add it to a debinding furnace, heat it from room temperature to 600-700°C at 1-3°C / min, keep it warm for 2-3h, then transfer it to a high-temperature sintering furnace, heat it to 1600-1900°C at 5-10°C / min in an argon atmosphere, and keep it warm for 3-6h.
[0020] Furthermore, the sintered ceramic green sheet is placed in an annealing furnace, cooled to 800-1000° C. at a rate of 2-5° C. / min, kept at that temperature for 1-2 hours, and then cooled to room temperature in the annealing furnace, and taken out to obtain a ceramic substrate.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. In the present invention, during the biological treatment of the ceramic slurry, the bio-template has a unique fibrous structure. Therefore, after the ceramic slurry is filled into the fiber gaps of the bio-template, the bio-template is decomposed through subsequent drying, pre-sintering and sintering treatments, while the fibrous microstructure of the bio-template is retained in the ceramic substrate. This fiber structure can absorb and disperse energy. When external force acts, the fiber can absorb energy by deformation, so that the ceramic substrate exhibits better toughness. At the same time, after decomposition, the bio-template will leave a certain pore structure in the ceramic substrate, which can increase the resistance to crack propagation, thereby improving the toughness and flexural strength of the ceramic substrate.
[0023] 2. In the present invention, by annealing the ceramic substrate, the atoms in the non-equilibrium position in the ceramic substrate can gradually migrate to a lower energy and more stable position under suitable temperature and slow cooling conditions, so that the lattice distortion is alleviated, thereby effectively eliminating the internal stress, improving the structural stability of the ceramic substrate, making its shape more regular, and reducing warping deformation. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below.
[0026] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.
[0027] Experiment 1:
[0028] The tape casting process for preparing a ceramic substrate comprises the following steps:
[0029] S1: Pretreatment, selecting high-purity ceramic powder, and placing it in a vacuum oven at 80°C for 4 hours to remove moisture and residual impurities, then adding the high-purity ceramic powder to the mixed liquid and stirring evenly to obtain a ceramic slurry;
[0030] S2: biological treatment, adding the biological template to the ceramic slurry, stirring and defoaming, and completing the biological treatment of the ceramic slurry;
[0031] S3: tape casting, placing the ceramic slurry in a tape casting machine for tape casting to obtain a ceramic green film;
[0032] S4: drying and pre-sintering treatment, drying and pre-sintering treatment of the ceramic green membrane obtained in S3, completing the drying and pre-sintering treatment of the ceramic green membrane;
[0033] S5: sintering treatment, cutting the ceramic green sheet that has completed the drying and pre-sintering treatment in S4, and then passing it through a debinding furnace, a high-temperature sintering furnace and an annealing furnace to complete debinding, sintering and annealing treatment, and then taking it out to obtain a ceramic substrate.
[0034] Furthermore, the mass ratio of the mixed liquid to the ceramic powder is 1:7, wherein the mixed liquid is composed of a dispersant, a binder, a plasticizer and a solvent, and the mass ratio thereof is 1:4:2:3.
[0035] Furthermore, the dispersant is at least one of ammonium polyacrylate or sodium dodecyl sulfate, the binder is at least one of polyvinyl alcohol or polymethyl methacrylate, the plasticizer is at least one of dibutyl phthalate or polyethylene glycol, and the solvent is at least one of ethanol or toluene.
[0036] Furthermore, the high-purity ceramic powder is at least one of aluminum oxide powder, aluminum nitride powder or zirconium oxide powder.
[0037] Furthermore, the bio-template is made by the following method: bamboo is selected as the material, and external dust and debris are removed by water washing. The bamboo is then soaked in a sodium hydroxide solution for 10 minutes, wherein the concentration of the sodium hydroxide solution is 1%, and then cut into long strips by a cutting machine to obtain the bio-template.
[0038] Furthermore, after cutting, the bio-template has a length of 3 cm, a width of 3 cm and a thickness of 1 mm.
[0039] Furthermore, the biological treatment step is: adding the bio-template into the ceramic slurry for soaking, wherein the mass ratio of the bio-template to the ceramic slurry is 1:8, and using a stirrer for auxiliary stirring, the stirring speed is 300r / min, and the stirring is carried out for 1h, then the ceramic slurry that is fully soaked and contains the bio-template is taken out, placed in a vacuum box for degassing treatment, and evacuated to a pressure below 500Pa for 20min to complete the biological treatment of the ceramic slurry.
[0040] Furthermore, the drying and pre-sintering treatment method is to place the ceramic green membrane in a drying oven, dry it at a temperature of 20°C and a relative humidity of 25% for 10 hours, then take out the dried ceramic green membrane, put it into a pre-sintering furnace, heat it to 400°C at a heating rate of 2°C / min in an air atmosphere, and keep it warm for 1 hour, thereby completing the drying and pre-sintering of the ceramic green membrane.
[0041] Furthermore, the sintering treatment method is to cut the dried and pre-sintered ceramic green membrane as needed, then add it to the debinding furnace, heat it from room temperature to 600°C at 1°C / min, keep it warm for 2 hours, then transfer it to a high-temperature sintering furnace, heat it to 1600°C at 5°C / min in an argon atmosphere, and keep it warm for 3 hours.
[0042] Furthermore, the sintered ceramic green sheet was placed in an annealing furnace, cooled to 800° C. at a rate of 2° C. / min, kept at that temperature for 1 hour, and then cooled to room temperature in the annealing furnace, and taken out to obtain a ceramic substrate.
[0043] Experiment 2:
[0044] The tape casting process for preparing a ceramic substrate comprises the following steps:
[0045] S1: Pretreatment, selecting high-purity ceramic powder, and placing it in a vacuum oven at 100°C for 6 hours to remove moisture and residual impurities, then adding the high-purity ceramic powder to the mixed liquid and stirring evenly to obtain a ceramic slurry;
[0046] S2: biological treatment, adding the biological template to the ceramic slurry, stirring and defoaming, and completing the biological treatment of the ceramic slurry;
[0047] S3: tape casting, placing the ceramic slurry in a tape casting machine for tape casting to obtain a ceramic green film;
[0048] S4: drying and pre-sintering treatment, drying and pre-sintering treatment of the ceramic green membrane obtained in S3, completing the drying and pre-sintering treatment of the ceramic green membrane;
[0049] S5: sintering treatment, cutting the ceramic green sheet that has completed the drying and pre-sintering treatment in S4, and then passing it through a debinding furnace, a high-temperature sintering furnace and an annealing furnace to complete debinding, sintering and annealing treatment, and then taking it out to obtain a ceramic substrate.
[0050] Furthermore, the mass ratio of the mixed liquid to the ceramic powder is 1:8, wherein the mixed liquid is composed of a dispersant, a binder, a plasticizer and a solvent, and the mass ratio thereof is 1:4:2:3.
[0051] Furthermore, the dispersant is at least one of ammonium polyacrylate or sodium dodecyl sulfate, the binder is at least one of polyvinyl alcohol or polymethyl methacrylate, the plasticizer is at least one of dibutyl phthalate or polyethylene glycol, and the solvent is at least one of ethanol or toluene.
[0052] Furthermore, the high-purity ceramic powder is at least one of aluminum oxide powder, aluminum nitride powder or zirconium oxide powder.
[0053] Furthermore, the bio-template is made by the following method: bamboo is selected as the material, and external dust and debris are removed by water washing. The bamboo is then soaked in a sodium hydroxide solution for 20 minutes, wherein the concentration of the sodium hydroxide solution is 2%, and then cut into long strips by a cutting machine to obtain the bio-template.
[0054] Furthermore, after cutting, the bio-template has a length of 4 cm, a width of 4 cm and a thickness of 1.5 mm.
[0055] Furthermore, the biological treatment step is: adding the bio-template into the ceramic slurry for soaking, wherein the mass ratio of the bio-template to the ceramic slurry is 1:9, and a stirrer is used for auxiliary stirring, the stirring speed is 300-500r / min, and the stirring is carried out for 1.5 hours. After that, the ceramic slurry that is fully soaked and contains the bio-template is taken out, placed in a vacuum box for degassing treatment, and evacuated to a pressure below 500Pa for a duration of 22.5 minutes to complete the biological treatment of the ceramic slurry.
[0056] Furthermore, the drying and pre-sintering treatment method is to place the ceramic green membrane in a drying oven, dry it at a temperature of 30°C and a relative humidity of 35% for 15 hours, then take out the dried ceramic green membrane, put it into a pre-sintering furnace, heat it to 500°C at a heating rate of 4°C / min in an air atmosphere, and keep it warm for 2 hours to complete the drying and pre-sintering of the ceramic green membrane.
[0057] Furthermore, the sintering treatment method is to cut the dried and pre-sintered ceramic green membrane as needed, then add it to the debinding furnace, heat it from room temperature to 650°C at 2°C / min, keep it warm for 3 hours, and then transfer it to a high-temperature sintering furnace, heat it to 1750°C at 7.5°C / min in an argon atmosphere, and keep it warm for 4.5 hours.
[0058] Furthermore, the sintered ceramic green sheet was placed in an annealing furnace, cooled to 900° C. at a rate of 3° C. / min, and kept at that temperature for 1.5 h. It was then cooled to room temperature in the annealing furnace and taken out to obtain a ceramic substrate.
[0059] Experiment 3:
[0060] The tape casting process for preparing a ceramic substrate comprises the following steps:
[0061] S1: Pretreatment, selecting high-purity ceramic powder, and placing it in a vacuum oven at 120°C for 8 hours to remove moisture and residual impurities, then adding the high-purity ceramic powder to the mixed solution and stirring evenly to obtain a ceramic slurry;
[0062] S2: biological treatment, adding the biological template to the ceramic slurry, stirring and defoaming, and completing the biological treatment of the ceramic slurry;
[0063] S3: tape casting, placing the ceramic slurry in a tape casting machine for tape casting to obtain a ceramic green film;
[0064] S4: drying and pre-sintering treatment, drying and pre-sintering treatment of the ceramic green membrane obtained in S3, completing the drying and pre-sintering treatment of the ceramic green membrane;
[0065] S5: sintering treatment, cutting the ceramic green sheet that has completed the drying and pre-sintering treatment in S4, and then passing it through a debinding furnace, a high-temperature sintering furnace and an annealing furnace to complete debinding, sintering and annealing treatment, and then taking it out to obtain a ceramic substrate.
[0066] Furthermore, the mass ratio of the mixed liquid to the ceramic powder is 1:9, wherein the mixed liquid is composed of a dispersant, a binder, a plasticizer and a solvent, and the mass ratio thereof is 1:4:2:3.
[0067] Furthermore, the dispersant is at least one of ammonium polyacrylate or sodium dodecyl sulfate, the binder is at least one of polyvinyl alcohol or polymethyl methacrylate, the plasticizer is at least one of dibutyl phthalate or polyethylene glycol, and the solvent is at least one of ethanol or toluene.
[0068] Furthermore, the high-purity ceramic powder is at least one of aluminum oxide powder, aluminum nitride powder or zirconium oxide powder.
[0069] Furthermore, the bio-template is made by the following method: bamboo is selected as the material, and external dust and debris are removed by water washing. The bamboo is then soaked in a sodium hydroxide solution for 30 minutes, wherein the concentration of the sodium hydroxide solution is 3%, and then cut into long strips by a cutting machine to obtain the bio-template.
[0070] Furthermore, after cutting, the bio-template has a length of 5 cm, a width of 5 cm and a thickness of 2 mm.
[0071] Furthermore, the biological treatment step is: adding the bio-template into the ceramic slurry for soaking, wherein the mass ratio of the bio-template to the ceramic slurry is 1:10, and using a stirrer for auxiliary stirring, the stirring speed is 500r / min, and the stirring is carried out for 2h, after which the ceramic slurry that is fully soaked and contains the bio-template is taken out, placed in a vacuum box for degassing treatment, and evacuated to a pressure below 500Pa for 25min to complete the biological treatment of the ceramic slurry.
[0072] Furthermore, the drying and pre-sintering treatment method is to place the ceramic green membrane in a drying oven, dry it at a temperature of 40°C and a relative humidity of 45% for 20 hours, then take out the dried ceramic green membrane, put it into a pre-sintering furnace, and heat it to 600°C at a heating rate of 6°C / min in an air atmosphere, and keep it warm for 3 hours to complete the drying and pre-sintering of the ceramic green membrane.
[0073] Furthermore, the sintering treatment method is to cut the dried and pre-sintered ceramic green membrane as needed, then add it to the debinding furnace, heat it from room temperature to 700°C at 3°C / min, keep it warm for 3 hours, and then transfer it to a high-temperature sintering furnace, heat it to 1900°C at 10°C / min in an argon atmosphere, and keep it warm for 3-6 hours.
[0074] Furthermore, the sintered ceramic green sheet was placed in an annealing furnace, cooled to 1000° C. at a rate of 5° C. / min, and kept at that temperature for 2 hours. After that, the annealing furnace was cooled to room temperature, and the ceramic substrate was taken out to obtain.
[0075] Comparative Example 1: The difference between this comparative example and Experiment 1 is that in this comparative example, no biological treatment is performed on the ceramic slurry.
[0076] Comparative Example 2: The difference between this comparative example and Experiment 1 is that in this comparative example, no annealing treatment is performed on the sintered ceramic green membrane.
[0077] Comparative Example 3: The difference between this comparative example and Experiment 1 is that in this comparative example, the ceramic slurry is not subjected to biological treatment and the sintered ceramic green membrane is not subjected to annealing treatment.
[0078] Performance test: The performance test was carried out on the ceramic substrates after being treated in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, and the obtained test data were recorded in the following table:
[0079] Table 1:
[0080]
[0081] In the flexural test, the flexural strength of the ceramic substrates made in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2 and Comparative Example 4 was measured using an SGL-8000 flexural strength tester;
[0082] In the toughness test, the toughness strength of the ceramic substrates made in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2 and Comparative Example 4 was measured using a QJ210A three-point bending tester.
[0083] By comparing and analyzing the relevant data in the table, it can be seen that the ceramic substrate processed by the tape casting method of the present invention not only has toughness strength, but also has excellent anti-bending effect. This shows that the tape casting method of preparing ceramic substrates provided by the present invention has a broader market prospect and is more suitable for promotion.
[0084] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0085] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A tape casting process for preparing a ceramic substrate, characterized in that: The following steps are involved: S1: Pretreatment, selecting high-purity ceramic powder, and placing it in a vacuum oven at 80-120°C for 4-8 hours to remove moisture and residual impurities, then adding the high-purity ceramic powder to the mixed liquid and stirring evenly to obtain a ceramic slurry; S2: biological treatment, adding the biological template to the ceramic slurry, stirring and defoaming, and completing the biological treatment of the ceramic slurry; S3: tape casting, placing the ceramic slurry in a tape casting machine for tape casting to obtain a ceramic green film; S4: drying and pre-sintering treatment, drying and pre-sintering treatment of the ceramic green membrane obtained in S3, completing the drying and pre-sintering treatment of the ceramic green membrane; S5: sintering treatment, cutting the ceramic green sheet that has completed the drying and pre-sintering treatment in S4, and then passing it through a debinding furnace, a high-temperature sintering furnace and an annealing furnace to complete debinding, sintering and annealing treatment, and then taking it out to obtain a ceramic substrate.
2. The tape casting process for preparing a ceramic substrate according to claim 1, characterized in that: The mass ratio of the mixed liquid to the ceramic powder is 1:(7-9), wherein the mixed liquid is composed of a dispersant, a binder, a plasticizer and a solvent, and the mass ratio thereof is 1:4:2:
3.
3. The tape casting process for preparing a ceramic substrate according to claim 1, characterized in that: The dispersant is at least one of ammonium polyacrylate or sodium dodecyl sulfate, the binder is at least one of polyvinyl alcohol or polymethyl methacrylate, the plasticizer is at least one of dibutyl phthalate or polyethylene glycol, and the solvent is at least one of ethanol or toluene.
4. The tape casting process for preparing a ceramic substrate according to claim 1, characterized in that: The high-purity ceramic powder is at least one of aluminum oxide powder, aluminum nitride powder or zirconium oxide powder.
5. The tape casting process for preparing a ceramic substrate according to claim 1, characterized in that: The biological template is made by the following method: bamboo is selected as the material, external dust and debris are removed by water washing, and then the bamboo is soaked in a sodium hydroxide solution for 10-30 minutes, wherein the concentration of the sodium hydroxide solution is 1%-3%, and then cut into long strips by a cutting machine to obtain the biological template.
6. The tape casting process for preparing a ceramic substrate according to claim 5, characterized in that: After cutting, the bio-template has a length of 3-5 cm, a width of 3-5 cm and a thickness of 1-2 mm.
7. The tape casting process for preparing a ceramic substrate according to claim 1, characterized in that: The biological treatment step is: adding the biological template into the ceramic slurry for soaking, wherein the mass ratio of the biological template to the ceramic slurry is 1: (8-10), and using a stirrer for auxiliary stirring, the stirring speed is 300-500r / min, and the stirring is carried out for 1-2h, then the ceramic slurry that is fully soaked and contains the biological template is taken out, placed in a vacuum box for degassing treatment, and evacuated to a pressure lower than 500Pa for a duration of 20-25min to complete the biological treatment of the ceramic slurry.
8. The tape casting process for preparing a ceramic substrate according to claim 1, characterized in that: The drying and pre-sintering treatment method is to place the ceramic green membrane in a drying oven, dry it for 10-20 hours at a temperature of 20-40°C and a relative humidity of 25-45%, then take out the dried ceramic green membrane, put it into a pre-sintering furnace, heat it to 400-600°C at a heating rate of 2-6°C / min in an air atmosphere, and keep it warm for 1-3 hours, thereby completing the drying and pre-sintering of the ceramic green membrane.
9. The tape casting process for preparing a ceramic substrate according to claim 1, characterized in that: The sintering treatment method is to cut the dried and pre-sintered ceramic green sheet as needed, then add it to a debinding furnace, heat it from room temperature to 600-700°C at 1-3°C / min, keep it warm for 2-3h, then transfer it to a high-temperature sintering furnace, heat it to 1600-1900°C at 5-10°C / min in an argon atmosphere, and keep it warm for 3-6h.
10. The tape casting process for preparing a ceramic substrate according to claim 9, characterized in that: The sintered ceramic green sheet is placed in an annealing furnace, cooled to 800-1000°C at a rate of 2-5°C / min, kept at that temperature for 1-2 hours, and then cooled to room temperature along with the annealing furnace, and taken out to obtain a ceramic substrate.
Citation Information
Patent Citations
Preparation method of ceramic substrate and ceramic substrate
CN118754620A